Assessment of Social Distance between Customers in Urban Hypermarket during COVID-19 Pandemic by Simulation Approach - Shahriari, Mehri; Feiz, Davood; Zarei, Azim; Kashi, Ehsan (Archives of Men’s Health, 2022)
Introduction: Social distance is important for reducing the spread of the new COVID-19 pandemic, especially in public places. In addition, urban stores are one of the crowded places where observing social distance is considered necessary. Therefore, the present study aimed to evaluate the social distance between customers in urban stores during the outbreak of the COVID-19 pandemic using a simulation method. Materials and methods: Research data were collected from the closed-circuit television footage of a store from a hypermarket in Iran, and then customers’ social distance was analyzed through their movement behaviors by two modes of 1 and 2-meter distance using software similar to the Pathfinder simulator. Further parts of the urban store required corrections considering the first scenario and the two-meter distance between people compared to the second scenario and the one-meter distance between them. Results: Based on simulation results, dense areas were identified in different sections of the hypermarket, namely, places where the shelves distance was 1 meter to 2 meters. More precisely, this research provided a method for evaluating different parts of the store in terms of population density regarding maintaining social distance. Conclusion: several suggestions were presented to stores for maintaining social distance based on research findings.